2021
DOI: 10.5194/acp-2021-591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eight-year variations in atmospheric radiocesium in Fukushima City

Abstract: Abstract. After the Fukushima nuclear accident, atmospheric 134Cs and 137Cs measurements were taken in Fukushima city for eight years, from March 2011 to March 2019. The surface air concentrations and deposition of radio-Cs were high in winter and low in summer; these trends are the opposite of those observed in a contaminated forest area. The half-lives of 137Cs in the concentrations and deposition before 2015 (275 d and 1.11 y) were significantly shorter than those after 2015 (756 d and 4.69 y). The dissolve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 22 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…The numerical simulations conducted by K16 were consistent with the findings described above: the surface concentrations in the mountainous forest area are low in winter and high in summer, the contributions of mineral dust are high in winter, and those of bioaerosols are high in summer. However, Watanabe et al (2021) found that the simulations of K16 underestimated the observed deposition amounts by approximately two orders of magnitude. The major reason for this large discrepancy in deposition is the incorrect assumption of the physical properties of resuspended 137 Cs by K16.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The numerical simulations conducted by K16 were consistent with the findings described above: the surface concentrations in the mountainous forest area are low in winter and high in summer, the contributions of mineral dust are high in winter, and those of bioaerosols are high in summer. However, Watanabe et al (2021) found that the simulations of K16 underestimated the observed deposition amounts by approximately two orders of magnitude. The major reason for this large discrepancy in deposition is the incorrect assumption of the physical properties of resuspended 137 Cs by K16.…”
Section: Introductionmentioning
confidence: 91%
“…1). The concentration and deposition measurements are conducted at Fukushima University (140.45°E, 37.68°N) (Watanabe et al, 2021). Fukushima University is located on a small hill at the southern edge of the Fukushima Basin and is surrounded by major roads.…”
Section: Observation Datamentioning
confidence: 99%
See 3 more Smart Citations